To Investigate The Association Between Current Car Seat Design With Body Posture For Reducing Musculoskeletal Disorders (MSD) Through Ergonomics Principles Among Malaysian Elderly - Yusoff, Irwan Syah Md; Majid, Ahmad Zuhairi Abdul (2016)
The elderly community may continue to serve their serviced after pension. Therefore, elderly drivers need to take specific consideration during driving activities according to ability and capability to sustain their life and minimizing injury’s and an accident. An ergonomics principles important to identify discomfort (mismatch) on seating posture based on National car seat design to sustain focus during driving according to Malaysian anthropometry measurement. This study also would determine association risk factors with current national car seat design and body posture at torso parts among elderly drivers within five’s year before pension and after five retirements. A cross - sectional study implementing and purposive method sampling used base on inclusive criteria; age 55 - 60 years old and five years after retirement (65 years old), self-driving and driving a national car. The Modified Nordic questionnaire was used to determine the prevalence Musculoskeletal Disorders (MSD) injury history . Rapid Upper Limb Assessment (RULA) apply into this study to observed risk level the seating body posture. SPSS software used to analyse data and CATIA software apply into a study for simulation analysis on seating risk level body posture with design intervention base on anthropometry elderly drivers measurement. The final outcome from the study may reveal either existing car seat design manufactured based on Malaysian population specifically to elderly and also identify the low back pain injury and musculoskeletal disorders symptom faced by the elderly driver caused from the current car seat design. Advantages of this study could determine the best seating body posture according to anthropometry dimension and improving elderly drivers health, safety and comfort and reducing the accident rate. Also, increase the ergonomic production of National car manufactured in car seat design